Clinical implications of dual therapy of acarbose plus myo-inositol on the thyroid profile in women with polycystic ovary syndrome - Marina Andavar; Raju Kamaraj; Thangavel Mahalingam Vijayakumar; Anuradha Murugesan (GarVal Editorial Ltda., 2024)
Context: Polycystic ovary syndrome (PCOS) and thyroid are the most common endocrine disorders affecting women of childbearing age, causing anovulation and infertility. There is an increased prevalence of thyroid dysfunction reported among PCOS women. Aims: To evaluate the benefits of acarbose plus myo-inositol therapy on the thyroid profile of PCOS. Methods: An open-labelled, parallel randomised clinical trial on 80 PCOS women based on inclusion and exclusion criteria was performed at the Department of Gynaecology, SRM Medical College Hospital and Research Centre, Kattankulathur. Institutional ethics committee approval and prior informed consent were obtained. The trial was registered in CTRI (No: CTRI/2022/04/041877). Group A (n = 38) received metformin 500 mg TID, and group B (n = 39) received acarbose 50 mg TID along with myoinositol 1000 mg BID. Assessment of metabolic and hormonal profile was done at baseline and at the end of six months. Results: Both groups showed significant reductions in luteinising hormone (p <0.0001), total testosterone (p<0.05), thyroid stimulating hormone (p<0.05), fasting insulin (p<0.05), and homeostatic model assessment for insulin resistance (p<0.0001). The follicle-stimulating hormone was increased only in the metformin group. No significant changes in body mass index, free triiodothyronine, free tetraiodothyronine, and fasting glucose were observed in any group. Both therapies were safe, and no side effects or hypoglycaemia were recorded. Conclusions: In consideration of the beneficial effects of the study, we conclude that the administration of acarbose plus myo-inositol exerts positive effects on the thyroid and other endocrinological profiles in PCOS women.